Microwave-Assisted Solvothermal Synthesis of Mo-Doped TiO2 with Exceptional Textural Properties and Superior Adsorption Kinetics - Yahia H. Ahmad (14340210) (2022)
Assigned to their outstanding physicochemical properties, TiO2-based materials have been studied in various applications. Herein, TiO2 doped with different Mo contents (Mo-TiO2) was synthesized via a microwave-assisted solvothermal approach. This was achieved using titanium (IV) butoxide and molybdenum (III) chloride as a precursor and dodecylamine as a surface directing agent. The uniform effective heating delivered by microwave heating reduced the reaction time to less than 30 min, representing several orders of magnitude lower than conventional heating methods. The average particle size ranged between 9.7 and 27.5 nm and it decreased with increasing the Mo content. Furthermore, Mo-TiO2 revealed mesoporous architectures with a high surface area ranging between 170 and 260 m2 g−1, which is superior compared to previously reported Mo-doped TiO2. The performance of Mo-TiO2 was evaluated towards the adsorption of Rhodamine B (RhB). In contrast to TiO2, which revealed negligible adsorption for RhB, Mo-doped samples depicted rapid adsorption for RhB, with a rate that increased with the increase in Mo content. Additionally, Mo-TiO2 expressed enhanced adsorption kinetics for RhB compared to state-of-the-art adsorbents. The introduced synthesis procedure holds a grand promise for the versatile synthesis of metal-doped TiO2 nanostructures with outstanding physicochemical properties. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano12122051